Constitutional Economics and Constitutional Financial Control - Valentina Viktorovna KOMAROVA; Vitaly Vladimirovich GOSHULYAK; Gleb Vladimirovich SINTSOV; Danil Evgenievich FEOKTISTOV (Communications of International Proceedings, 2021)
The issues of legal formalization of the economic content of such fundamental legal values ​​as freedom, equality and justice in constitutional regulation are becoming increasingly relevant in the modern legal reality of the Russian Federation. The crisis caused by the COVID-19 pandemic in 2020 has brought significant changes to many areas of society and state. The conditions for the functioning of public and public institutions have changed. Within the framework of new economic relations, their participants are forced to adapt to the prevailing conditions and look for solutions to emerging difficulties. In this regard, there is a need for an objective assessment of the content and effectiveness of those constitutional norms that are designed to legally determine socio-economic priorities, ensure the stability of economic relations and the implementation of the principle of social justice. The Constitution of the Russian Federation, all its sections in their organic unity are related to the economic development of the country and the provision of social justice in society, setting the basis for their functioning and the logical implementation of constitutional values. The practical tasks of constitutional economics include identifying the constitutional and legal prerequisites for the effective development of the economy, analyzing the impact of the economy on the state, studying the crisis impact of the economy on the state and vice versa. The implementation of the tasks facing the constitutional economy presupposes the presence of an obligatory element - control over their implementation. The article poses the problem of determining the role of constitutional financial control in solving the problems facing the constitutional economics. Financial control involves not only a formal check of planned indicators for their compliance with established standards, but also includes the development and further implementation of measures to prevent and minimize deviations and violations, determining the directions for increasing efficiency in the given parameters. The implementation of these functions is carried out by a special constitutional body of parliamentary financial control - the Accounts Chamber of the Russian Federation. The article is a continuation of the study "Constitutional Economics: Importance for Modern Russia", published at the 34th IBIMA Conference.
Keywords: The constitutional economy; constitutional control; economic development; the Accounts Chamber of the Russian Federation